Peran Perbankan Syariah Dalam Mengembangkan UMKM (Usaha Mikro Kecil Menegah) Di Kabupaten Lombok Timur Ditinjau Berdasarkan Pasal 3 Uu No. 21 Tahun 2008 Tentang Perbankan Syariah : The Role Of Sharia Banking In Developing UMKM(Micro Small Medium Enterprises) In East Lombok Regency Reviewed Based On Article 3 Of Law No. 21 Of 2008 Concerning Sharia Banking - HASAN ASARI (Fakultas Hukum Universitas Gunung Rinjani, 2023)
The aim of this research is to find out the role and impact of micro and medium enterprises on the existence of Sharia banks in Pringgabaya district. In preparing and writing this research, the writer needs concrete data as material for discussing the writing of this thesis. This type of research is empirical normative legal research (applied law research), and it includes interviews and direct observations of actual human behavior, and Normative Law is a process for finding legal rules, legal principles, and legal doctrines in order to answer the legal issues faced. And as for the benefits in this study as information material about the role of Islamic banks. The results of interviews conducted by researchers with customers and with the business manager of one of the sharia banks in the Pringgabaya district can be analyzed that the existence of a Sharia Bank in East Lombok regency has provided results and impacts for micro and medium businesses in the Pringgabaya district. This can be seen from the customer's business which is getting better after financing at Islamic Banks. Apart from that, customers also felt an increase in income, an increase in sales volume, and the addition of new employees to their business after financing at the Sharia Bank in Pringgabaya district.